Composite particles for non-aqueous electrolyte secondary battery and non-aqueous electrolyte secondary battery
Patent Information
- Application Number
- JP2023131857
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-08-14
- Publication Date
- 2025-02-27
AI Technical Summary
【0009】 このように構成した非水電解質二次電池用複合粒子によれば、金属水酸化物だけでなく、難燃化成分を十分量含有させることにより電池の内部温度上昇を従来よりもさらに抑制できるだけでなく、これらを含有させることによる電池のサイクル特性の悪化を抑制することができる。
Smart Images

Figure 2025027230000003 
Figure 2025027230000004 
Figure 2025027230000001
Abstract
Description
[Technical field]
[0001] The present invention relates to composite particles for non-aqueous electrolyte secondary batteries and non-aqueous electrolyte secondary batteries containing the same. [Background technology]
[0002] Non-aqueous electrolyte secondary batteries, including lithium-ion secondary batteries, are widely used as power sources for devices such as smartphones and laptop computers, and more recently have also been used as large batteries for vehicles. On the other hand, while lithium ion secondary batteries have the advantage of high energy density, they require sufficient safety measures because of the use of a non-aqueous electrolyte. In recent years, as batteries have become larger, ensuring safety has become even more important.
[0003] For example, if a lithium-ion secondary battery is placed in a high-temperature environment, the positive electrode of the lithium-ion secondary battery may generate heat, or heat may be generated due to an oxidative decomposition reaction of the electrolyte caused by oxygen radicals generated from the positive electrode, which may cause an increase in the internal temperature of the battery. If the internal temperature of the battery becomes very high due to such reasons, the separator in the lithium-ion secondary battery will shrink, making it more likely to cause a short circuit, which could further increase the internal temperature of the battery.
[0004] In view of this, as a method for suppressing the rise in internal temperature of a lithium-ion secondary battery and ensuring safety, there have been proposed methods for incorporating a binder containing a radical scavenger such as a phosphate ester having radical scavenging ability (Patent Document 1) or for incorporating metal hydroxide particles having heat absorption properties (Patent Documents 2 and 3). [Prior art documents] [Patent documents]
[0005] [Patent Document 1] JP 2011-159484 A [Patent Document 2] JP 2016-162528 A [Patent Document 3] JP 2011-258481 A Summary of the Invention [Problem to be solved by the invention]
[0006] However, according to the study by the present inventors, it has been found that there are cases where the rise in the internal temperature of a battery cannot be sufficiently suppressed by simply incorporating the radical scavenger described in Patent Document 1 or the metal hydroxide particles described in Patent Documents 2 and 3 into a nonaqueous electrolyte secondary battery such as a lithium ion secondary battery. The present inventors have also noticed that there are problems such as deterioration of cycle characteristics (discharge capacity retention rate) when charge / discharge cycles are repeated by incorporating metal hydroxide particles or a radical scavenger.
[0007] The present invention was completed only after the inventors, through extensive research, discovered that by containing a metal hydroxide and a flame retardant component and by setting the content of a specific element that constitutes the flame retardant component within a prescribed range, it is possible to not only solve the above-mentioned problems but also to obtain an even greater effect of suppressing internal temperature rise. [Means for solving the problem]
[0008] That is, the present invention includes the following. [1] A composite particle for a non-aqueous electrolyte secondary battery, comprising a metal hydroxide and a flame retardant component, The flame retardant component contains phosphorus or phosphorus and boron or bromine, The composite particles for a non-aqueous electrolyte secondary battery have a phosphorus content, or a total content of phosphorus and boron or bromine, in 100 mass % of the composite particles for a non-aqueous electrolyte secondary battery, of 18 mass % or more and 30 mass % or less. [2] The amount of P2 desorbed from the composite particles at 80°C to 1400°C (MS1) was 600 x 10 -6mol / g or more 2000×10 -6 mol / g or less, and the amount of H2O desorbed from 80°C to 200°C by TDS-MS (MS2) is 50×10 -6 mol / g or more 1000×10 -6 The composite particles for non-aqueous electrolyte secondary batteries have a molecular weight of 1.0 mol / g or less. [3] The amount of CH4 desorbed from 80°C to 1400°C (MS3) was 30×10 -6 mol / g or more 400×10 -6 mol / g or less, and the amount of CH3OH desorbed from the composite particles at temperatures between 80°C and 1400°C by TDS-MS (MS4) is 500 x 10 -6 mol / g or more 2500×10 -6 mol / g or less, and the amount of C6H6 desorbed from 80°C to 1400°C by TDS-MS (MS5) is 100×10 -6 mol / g or more 2500×10 -6 mol / g or less. [4] The composite particles for a nonaqueous electrolyte secondary battery according to [2], wherein the ratio of the amounts of desorbed gas satisfies the following formula (1): 0.6≦(MS1 / MS2)≦10.0 (1) [5] The BET specific surface area calculated from the nitrogen adsorption isotherm is 8 m 2 / g or more 80m 2 The composite particles for a non-aqueous electrolyte secondary battery according to any one of [1] to [4], wherein the particle size is 0.1 to 0.5 μg / g or less. [6] The composite particles for use in a non-aqueous electrolyte secondary battery according to any one of [1] to [5], wherein the composite particles have a cumulative 50% (D50) value of a volume-based particle size distribution of 0.05 μm or more and 10 μm or less. [7] The composite particles for a non-aqueous electrolyte secondary battery according to any one of [1] to [6], wherein the metal hydroxide comprises at least one selected from the group consisting of aluminum hydroxide, pseudoboehmite, boehmite, activated alumina, and kaolinite. [8] The composite particles for non-aqueous electrolyte secondary batteries according to any one of [1] to [7], wherein the aluminum element content measured by inductively coupled plasma atomic emission spectrometry (ICP-AES) is 5% by mass or more and 30% by mass or less. [9] A positive electrode for a nonaqueous electrolyte secondary battery comprising a positive electrode current collector and a positive electrode mixture layer laminated on the positive electrode current collector, The positive electrode mixture layer contains a positive electrode active material and the composite particle for a non-aqueous electrolyte secondary battery according to any one of [1] to [8].
[10] A nonaqueous electrolyte secondary battery comprising a positive electrode, a negative electrode, a separator, and a nonaqueous electrolyte solution, wherein the positive electrode is the positive electrode for a nonaqueous electrolyte secondary battery according to [9].
[11] A method for producing the composite particles for a non-aqueous electrolyte secondary battery according to [1], comprising a step of mixing metal hydroxide particles and a flame retardant and heating the mixture. Effect of the Invention
[0009] According to the composite particles for a nonaqueous electrolyte secondary battery thus configured, by containing a sufficient amount of not only a metal hydroxide but also a flame retardant component, it is possible to suppress the rise in the internal temperature of the battery more than ever before, and also to suppress the deterioration of the cycle characteristics of the battery due to the inclusion of these components. [Brief description of the drawings]
[0010] [Figure 1] 3 is a graph showing cycle characteristics in an example of the present invention and a comparative example. [Diagram 2] Graph showing the heat generation suppression effect in the examples of the present invention and the comparative examples. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0011] A specific configuration of a nonaqueous electrolyte secondary battery according to one embodiment of the present invention will be described below. <1. Basic structure of non-aqueous electrolyte secondary battery> The nonaqueous electrolyte secondary battery according to this embodiment is a lithium ion secondary battery including a positive electrode, a negative electrode, a separator, and a nonaqueous electrolyte. The shape of the lithium ion secondary battery is not particularly limited, but may be, for example, any of a cylindrical shape, a rectangular shape, a laminate shape, a button shape, and the like.
[0012] (1-1. Positive electrode) The positive electrode includes a positive electrode current collector and a positive electrode mixture layer formed on the positive electrode current collector. The positive electrode current collector may be any conductive material, for example, a plate or foil, and is preferably made of aluminum, stainless steel, nickel-plated steel, or the like. The positive electrode mixture layer contains a positive electrode active material, and may further contain a conductive agent and a positive electrode binder.
[0013] The positive electrode active material is, for example, a transition metal oxide or solid solution oxide containing lithium, and is not particularly limited as long as it is a material that can electrochemically absorb and release lithium ions. Examples of the transition metal oxide containing lithium include Li 1.0 Ni 0.88 Co 0.1 Al 0.01 Mg 0.01 O2, etc., but also LiCoO2 and other Li·Co-based composite oxides, LiNi x Co y Mn z Examples of the solid solution oxide include Li·Ni·Co·Mn-based composite oxides such as LiO2, Li·Ni-based composite oxides such as LiNiO2, and Li·Mn-based composite oxides such as LiMn2O4. a Mn x Co y Ni z O2 (1.150≦a≦1.430, 0.45≦x≦0.6, 0.10≦y≦0.15, 0.20≦z≦0.28), LiMn 1.5 Ni 0.5Examples of the positive electrode active material include O4 and the like. The content (content ratio) of the positive electrode active material is not particularly limited, and may be any content that is applicable to the positive electrode mixture layer of the non-aqueous electrolyte secondary battery. These compounds may be used alone or in combination.
[0014] The conductive agent is not particularly limited as long as it is capable of increasing the conductivity of the positive electrode. Specific examples of the conductive agent include those containing one or more selected from carbon black, natural graphite, artificial graphite, fibrous carbon, and sheet carbon. Examples of the carbon black include furnace black, channel black, thermal black, ketjen black, and acetylene black. Examples of the fibrous carbon include carbon nanotubes and carbon nanofibers, and examples of the sheet-like carbon include graphene. The content of the conductive agent in the positive electrode mixture layer is not particularly limited, but from the viewpoint of achieving both electrical conductivity and battery capacity, the content is preferably 0.1 mass % or more and 5 mass % or less, and more preferably 0.5 mass % or more and 3 mass % or less, based on the entire positive electrode mixture layer.
[0015] Examples of the positive electrode binder include fluorine-containing resins such as polyvinylidene fluoride, ethylene-containing resins such as styrene-butadiene rubber, ethylene-propylene-diene terpolymer, acrylonitrile-butadiene rubber, fluororubber, polyvinyl acetate, polymethylmethacrylate, polyethylene, polyvinyl alcohol, carboxymethyl cellulose or carboxymethyl cellulose derivatives (salts of carboxymethyl cellulose, etc.), or nitrocellulose. The positive electrode binder is not particularly limited as long as it can bind the positive electrode active material and the conductive agent onto the positive electrode current collector.
[0016] (1-2. Negative electrode) The negative electrode includes a negative electrode current collector and a negative electrode mixture layer formed on the negative electrode current collector. The negative electrode current collector may be any conductive material, and is preferably, for example, in the form of a plate or foil, and is made of copper, stainless steel, nickel-plated steel, or the like.
[0017] The negative electrode mixture layer contains a negative electrode active material, and may further contain a conductive agent and a negative electrode binder. The negative electrode active material is not particularly limited as long as it can electrochemically absorb and release lithium ions. Examples of the negative electrode active material include graphite active materials (artificial graphite, natural graphite, a mixture of artificial graphite and natural graphite, natural graphite coated with artificial graphite, etc.), Si-based active materials or Sn-based active materials (for example, a mixture of fine particles of silicon (Si) or tin (Sn) or an oxide thereof and a graphite active material, fine particles of silicon or tin, and an alloy based on silicon or tin), metallic lithium, and Li4Ti5O 12 Examples of the negative electrode active material include titanium oxide compounds such as lithium nitride and lithium carbide. As the negative electrode active material, one of the above may be used, or two or more of them may be used in combination. The oxide of silicon is represented by SiOx (0≦x≦2).
[0018] The conductive agent is not particularly limited as long as it is capable of increasing the conductivity of the negative electrode, and for example, the same conductive agent as that described in the section regarding the positive electrode can be used. The content of the conductive agent in the negative electrode mixture layer is not particularly limited, but from the viewpoint of achieving both electrical conductivity and battery capacity, the content is preferably 0.1 mass % or more and 5 mass % or less, and more preferably 0.5 mass % or more and 3 mass % or less, based on the entire negative electrode mixture layer.
[0019] The negative electrode binder is not particularly limited as long as it can bind the negative electrode active material and the conductive agent on the negative electrode current collector. The negative electrode binder may be, for example, polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), polyacrylic acid (PAA), styrene butadiene copolymer (SBR), metal salt of carboxymethyl cellulose (CMC), etc. One type of binder may be used alone, or two or more types may be used.
[0020] (1-3. Separator) The separator is not particularly limited, and may be any separator that can be used as a separator for a lithium ion secondary battery. As the separator, it is preferable to use a porous membrane or a nonwoven fabric that exhibits excellent high-rate discharge performance, either alone or in combination. Examples of resins constituting the separator include polyolefin resins such as polyethylene and polypropylene, polyester resins such as polyethylene terephthalate and polybutylene terephthalate, polyvinylidene difluoride, vinylidene fluoride-hexafluoropropylene copolymer, vinylidene difluoride-perfluorovinyl ether copolymer, vinylidene difluoride-tetrafluoroethylene copolymer, vinylidene difluoride-trifluoroethylene copolymer, vinylidene difluoride- ... copolymer, vinylidene difluoride-hexafluoroacetone copolymer, vinylidene difluoride-ethylene copolymer, vinylidene difluoride-propylene copolymer, vinylidene difluoride-trifluoropropylene copolymerExamples of the separator include vinylidene fluoride-tetrafluoroethylene-hexafluoropropylene copolymer, vinylidene difluoride-tetrafluoroethylene copolymer, vinylidene difluoride-ethylene-tetrafluoroethylene copolymer, etc. The porosity of the separator is not particularly limited, and the porosity of the separator of a conventional lithium ion secondary battery can be arbitrarily applied.
[0021] The separator may further include a surface layer that covers the surface of the porous membrane or nonwoven fabric. The surface layer may include an adhesive for bonding with the electrodes to fix the battery element. Examples of the adhesive include vinylidene fluoride-hexafluoropropylene copolymer, an acid-modified vinylidene fluoride polymer, and a styrene-(meth)acrylic acid ester copolymer.
[0022] (1-4.Non-aqueous electrolyte) The nonaqueous electrolyte may be the same as the nonaqueous electrolyte conventionally used in lithium ion secondary batteries, without any particular limitation. The nonaqueous electrolyte has a composition in which an electrolyte salt is contained in a nonaqueous solvent, which is a solvent for the electrolyte. Examples of the non-aqueous solvent include cyclic carbonates such as propylene carbonate, ethylene carbonate, butylene carbonate, chloroethylene carbonate, fluoroethylene carbonate, and vinylene carbonate; cyclic esters such as γ-butyrolactone and γ-valerolactone; chain carbonates such as dimethyl carbonate, diethyl carbonate, and ethylmethyl carbonate; methylformate, methylacetate, methylbutyrate, ethyl propionate, and propyl propionate. propionate, tetrahydrofuran or its derivatives, 1,3-dioxane, 1,4-dioxane, 1,2-dimethoxyethane, 1,4-dibutoxyethane (1,4-dibutoxyethane, methyldiglyme, ethers such as ethylene glycol monopropyl ether, propylene glycol monopropyl ether, nitriles such as acetonitrile, benzonitrile, dioxolane or a derivative thereof, ethylene sulfide, sulfolane, sultone or a derivative thereof, etc., can be used alone or in combination of two or more kinds. When two or more kinds of the nonaqueous solvents are used in combination, the mixing ratio of the nonaqueous solvents can be the same as that used in conventional lithium ion secondary batteries.
[0023] Examples of electrolyte salts include LiClO4, LiBF4, LiAsF6, LiPF6, and LIPF6-x (C n F 2n+1 )x[where 1 <x<6、n=1or2]、LiSCN、LiBr、LiI、Li2SO4、Li2B 10 Cl 10, NaClO4, NaI, NaSCN, NaBr, KClO4, KSCN and other inorganic ion salts containing one of lithium (Li), sodium (Na) or potassium (K), LiCF3SO3, LiN(CF3SO2)2, LiN(C2F5SO2)2, LiN(CF3SO2)(C4F9SO2), LiC(CF3SO2)3, LiC(C2F5SO2)3, (CH3)4NBF4, (CH3)4NBr, (C2H5)4NClO4, (C2H5)4NI, (C3H7)4NBr, (n-C4H9)4NClO4, (n-C4H9)4NI, (C2H5)4N-maleate, (C2H5)4N-benzoate, (C2H5)4N-phtalate, lithium stearyl sulfonic acid Examples of suitable ionic compounds include organic ionic salts such as lithium, octyl sulfonic acid lithium, and dodecyl benzenesulfonic acid lithium. These ionic compounds can be used alone or in combination of two or more. The concentration of the electrolyte salt may be the same as that of the non-aqueous electrolyte used in conventional lithium ion secondary batteries, and is not particularly limited. In this embodiment, it is preferable to use a non-aqueous electrolyte containing the above-mentioned lithium compound (electrolyte salt) at a concentration of about 0.8 mol / L or more and 1.5 mol / L or less.
[0024] In addition, various additives may be added to the non-aqueous electrolyte. Examples of such additives include negative electrode additives, positive electrode additives, ester additives, carbonate additives, sulfate additives, phosphate additives, borate additives, acid anhydride additives, and electrolyte additives. Any one of these may be added to the non-aqueous electrolyte, or multiple types of additives may be added to the non-aqueous electrolyte.
[0025] 2. Characteristics and configuration of the nonaqueous electrolyte secondary battery according to the present embodiment The characteristic configuration of the nonaqueous electrolyte secondary battery according to this embodiment will be described below. The positive electrode mixture layer of the nonaqueous electrolyte secondary battery according to this embodiment contains, in addition to the above-mentioned components, composite particles for nonaqueous electrolyte secondary batteries (also simply referred to as composite particles) that function as a heat-inhibiting additive that inhibits an internal temperature rise in the battery.
[0026] The composite particles are obtained by heating and compounding a metal hydroxide capable of absorbing heat by an endothermic reaction with a flame retardant having a radical scavenging ability. The composite particles are obtained by compounding the metal hydroxide and the flame retardant in a state where they are mixed as uniformly as possible. More specifically, the composite particles are a collection of a plurality of metal hydroxide particles in a state where the flame retardant component derived from the flame retardant is contained on the surface and inside thereof. Here, the composite refers to, for example, a state in which a plurality of particles are chemically bonded to each other via functional groups (e.g., hydroxyl groups and phosphate groups, etc.) possessed by metal hydroxide particles in a state where the flame retardant component is contained on the surface and inside thereof, forming a single mass. The chemical bond here includes not only covalent bonds but also various bonds such as ionic bonds, coordinate bonds, and metallic bonds. The bonding state between particles can be confirmed, for example, by X-ray photoelectron spectroscopy.
[0027] The particle size of the composite particles is preferably such that the integrated value 50% (D50) of the volume-based particle size distribution is 0.05 μm or more and 10 μm or less, more preferably 0.08 μm or more and 9 μm or less, and particularly preferably 0.1 μm or more and 8.5 μm or less. The particle size of the composite particles can be controlled by the conditions for producing the composite particles. For example, increasing the temperature or the stirring speed during the production of the composite particles tends to reduce the particle size of the composite particles. For example, it is possible to make the particle size of the composite particles smaller than the particle size of the metal hydroxide, which is the starting material.
[0028] In addition, the BET specific surface area of the composite particles calculated from the adsorption isotherm measured by adsorbing nitrogen to the composite particles is 8 m 2 / g or more 80m 2 / g or less, and 2 / g or more 75m 2 / g or less is more preferable, and 15m 2 / g or more 75m 2 It is particularly preferable that the molecular weight is not more than 1 / g.
[0029] The metal hydroxide is not particularly limited as long as it is an endothermic substance capable of causing an endothermic reaction. Specific examples of the metal hydroxide include aluminum hydroxide, pseudoboehmite, boehmite, activated alumina, and kaolinite. These may be used alone or in combination of two or more kinds.
[0030] The integrated value 50% (D50) of the volume-based particle size distribution of the metal hydroxide particles is preferably 10 nm or more and 10 μm or less, more preferably 0.1 μm or more and 8 μm or less, and even more preferably 0.5 μm or more and 5 μm or less.
[0031] The content of hydroxide particles in the composite particles is preferably in the range of 1% by mass or more and 60% by mass or less, more preferably in the range of 5% by mass or more and 50% by mass or less, and even more preferably in the range of 10% by mass or more and 40% by mass or less, based on the entire composite particle (100% by mass).
[0032] The flame retardant may be any flame retardant having a radical scavenging ability to capture radicals such as oxygen radicals generated in the positive electrode mixture layer. For example, the flame retardant is preferably one or more selected from the group consisting of phosphoric acid, phosphate ester, phosphonic acid, phosphonic acid ester, phosphinic acid, and phosphinic acid ester, which are capable of forming a functional group containing phosphorus (P) element by combining with the metal hydroxide. Examples of the phosphate ester include phenyl phosphate, diphenyl phosphate, and triphenyl phosphate. Examples of the phosphonic acid ester include phenylphosphonic acid and methylphosphonic acid. An example of the phosphinic acid ester is methylphosphinic acid.
[0033] The content of P (phosphorus) element, the total content of P (phosphorus) element and B (boron) element, or the total content of P (phosphorus) element and Br (bromine) element of the composite particles measured by an inductively coupled plasma atomic emission spectrometer (ICP-AES) is within a range of 18% by mass to 30% by mass with respect to the entire composite particles (100% by mass). The content or total content of these elements is more preferably 18% by mass to 25% by mass.
[0034] The content of P (phosphorus) element in the composite particles is preferably 5% by mass or more and 30% by mass or less, and more preferably 8% by mass or more and 30% by mass or less. The content of B (boron) element in the composite particles may be 0, or may be 1 mass % or more and 25 mass % or less, or may be 5 mass % or more and 15 mass % or less. The content of Br (bromine) element in the composite particles may be 0, or may be 1% by mass or more and 25% by mass or less, or may be 5% by mass or more and 10% by mass or less.
[0035] The content of Al (aluminum) element in the composite particles measured by ICP-AES may be 0, but is preferably 1% by mass to 30% by mass or less, more preferably 3% by mass to 20% by mass or less, and particularly preferably 5% by mass to 15% by mass or less.
[0036] The composite particles preferably have various outgassing amounts caused by various modifying groups within the following ranges. The amount of P2 gas desorbed from the composite particles when the composite particles were heated from 80° C. to 1400° C. was measured by a temperature programmed desorption gas mass spectrometer (TDS-MS), and the amount of desorbed P2 (referred to as MS1) was 600×10 -6 mol / g or more 2000×10 -6 mol / g or less, and the amount of H2O gas desorbed from the composite particles when the composite particles are heated from 80°C to 200°C is measured by TDS-MS and the amount of desorbed H2O (referred to as MS2) is 50 x 10 -6mol / g or more 1000×10 -6 It is preferably mol / g or less. MS1 is 620 x 10 -6 mol / g or more 1900×10 -6 mol / g or less is more preferable, and 630×10 -6 mol / g or more 1800×10 -6 It is particularly preferable that the amount is mol / g or less. MS2 is 100 x 10 -6 mol / g or more 950×10 -6 It is more preferable that the concentration is 200×10 -6 mol / g or more 900×10 -6 It is particularly preferable that the amount is mol / g or less.
[0037] Furthermore, the ratio of the gas release amounts (M1 / M2) is preferably 0.6 to 10.0, more preferably 0.7 to 5.0, and particularly preferably 0.8 to 4.0. When the ratio of the gas release amounts (M1 / M2) satisfies this preferred range, it is possible to achieve a better balance between the temperature rise suppression effect and the battery performance achieved by increasing the content of the flame retardant component in the composite particles.
[0038] Increasing the content of phosphorus in the composite particles improves the effect of suppressing the temperature rise inside the battery. On the other hand, if the amount of flame retardant such as phosphoric acid or phosphonic acid added is increased in order to increase the content of phosphorus, the hydrophilicity of the composite particles increases, making it difficult to uniformly mix the composite particles in the slurry for forming the positive electrode mixture layer. The present inventors, who have been diligently studying this problem, have found that by using not only phosphoric acid or phosphonic acid with a large content of phosphorus, but also a flame retardant containing a hydrophobic group such as a phosphoric acid ester or a phosphonic acid ester in combination, it is possible to suppress the hydrophilicity from becoming too high while increasing the content of phosphorus more than ever before. The content of hydrophobic groups in the composite particles can be evaluated by the amount of desorption of the following various gases derived from each hydrophobic group in the composite particles, and it is preferable that the amount of desorption of various gases satisfies the following range.
[0039] The amount of CH4 gas desorbed from the composite particles when the composite particles are heated from 80° C. to 1400° C. is measured by TDS-MS. The amount of desorbed CH4 (MS3) may be 0, but may be 30 -6 mol / g or more 400×10 -6 mol / g or less, and preferably 40×10 -6 mol / g or more 350×10 -6 mol / g or less is more preferable, and 50×10 -6 mol / g or more 300×10 -6 It is particularly preferable that the amount is mol / g or less. The amount of desorbed CH3OH (MS4) measured in the same manner may be 0, but may be 500 -6 mol / g or more 2500×10 -6 It is preferable that the concentration is 600×10 -6 mol / g or more 2450×10 -6 mol / g or less is more preferable, and 700×10 -6 mol / g or more 2400×10 -6 It is particularly preferable that the amount is mol / g or less.
[0040] When the composite particles are modified with a functional group containing a hydrophobic group, particularly a phenyl group, the composite particles are more easily dispersed in a non-aqueous solvent such as N-methyl-2-pyrrolidone (NMP) when a slurry is prepared using the solvent. Therefore, the amount of C6H6 desorbed from the composite particles at temperatures between 80°C and 1400°C by TDS-MS (referred to as MS5) may be 0, but it is preferable that the amount of C6H6 desorbed from the composite particles at temperatures between 80°C and 1400°C be 100 -6 mol / g or more 2500×10 -6 mol / g or less, and preferably 300×10 -6 mol / g or more 2400×10 -6 mol / g or less is more preferable, and 600×10 -6 mol / g or more 2300×10 -6 It is particularly preferable that the amount is mol / g or less.
[0041] The content of the composite particles in the positive electrode mixture layer is preferably in the range of 0.1% by mass to 5% by mass, more preferably 0.2% by mass to 3% by mass, and particularly preferably 0.5% by mass to 2% by mass, assuming that the entire positive electrode mixture layer is 100% by mass. If the content is in such a range, sufficient heat generation suppression effect and good battery performance can be exhibited.
[0042] Furthermore, the content of the composite particles for non-aqueous electrolyte secondary batteries in the entire non-aqueous electrolyte secondary battery varies depending on the application of the non-aqueous electrolyte secondary battery and is not limited to the following range; however, for example, when the mass of the entire non-aqueous electrolyte secondary battery is taken as 100 mass%, the content of the composite particles for non-aqueous electrolyte secondary batteries contained in the non-aqueous electrolyte secondary battery is preferably 0.01 mass% or more and 5.0 mass% or less, more preferably 0.02 mass% or more and 2.0 mass% or less, and particularly preferably 0.1 mass% or more and 0.5 mass% or less.
[0043] <3. Method for manufacturing the nonaqueous electrolyte secondary battery according to the present embodiment> Next, a method for manufacturing the lithium ion secondary battery according to this embodiment will be described. (3-1. Method for producing composite particles) The composite particles for a non-aqueous electrolyte secondary battery according to this embodiment can be produced by mixing metal hydroxide particles and a flame retardant and heating the mixture. The mixing can be carried out, for example, by heating a dispersion in which metal hydroxide particles and a flame retardant are dispersed in a suitable solvent to a temperature of, for example, 40°C or higher and 100°C or lower, reacting the mixture at that temperature for 1 hour or higher and 48 hours or lower, and then filtering the mixture through filter paper to obtain composite particles. The solvent preferably contains water, and is preferably a mixture of water and an alcohol-based organic solvent such as ethanol or 2-propanol. The heating temperature is preferably from 60° C. to 80° C., and the heating time (reaction time) is preferably from 5 hours to 30 hours.
[0044] In order to obtain composite particles in which the metal hydroxide is modified with a larger amount of flame retardant components derived from the flame retardant, it is preferable to use a metal hydroxide as the starting material with as large a BET specific surface area as possible, and it is preferable to set the BET specific surface area of the composite particles obtained by mixing a flame retardant with a metal hydroxide having a relatively large BET specific surface area and compositing them to be within the above-mentioned range. The BET specific surface area of the composite particles tends to be smaller when the amount of flame retardant added to the metal hydroxide is increased or the reaction time when the metal hydroxide and the flame retardant are combined is extended. Therefore, since the BET specific surface area of the composite particles can be adjusted by changing these conditions, the BET specific surface area of the metal hydroxide as the starting material is not particularly limited, but the BET specific surface area of the metal hydroxide is preferably within 100 m, for example. 2 / g or more 500m 2 It is preferable that the molecular weight is not more than 1 / g.
[0045] (3-2. Method for producing positive electrode) The positive electrode is produced as follows. First, a positive electrode active material, a conductive agent, a positive electrode binder, and the composite particles are mixed in a desired ratio and dispersed in a positive electrode slurry solvent to form a positive electrode slurry. Next, the positive electrode slurry is applied onto a positive electrode current collector and dried to form a positive electrode mixture layer. The application method is not particularly limited. Examples of the application method include a knife coater method, a gravure coater method, a reverse roll coater, and a slit die coater. The following application steps are also performed in the same manner. Next, the positive electrode mixture layer is pressed to a desired density by a press machine. This produces a positive electrode.
[0046] (3-3. Method for producing negative electrode) The negative electrode is also prepared in the same manner as the positive electrode. First, a mixture of materials constituting the negative electrode mixture layer is dispersed in a solvent for the negative electrode slurry to prepare a negative electrode slurry. Next, the negative electrode slurry is applied onto a negative electrode current collector and dried to form a negative electrode mixture layer. Next, the negative electrode mixture layer is pressed by a press machine to a desired density. This completes the negative electrode.
[0047] (3-4. Method for manufacturing non-aqueous electrolyte secondary battery) Next, the separator is sandwiched between the positive and negative electrodes to produce an electrode structure. The electrode structure is then processed into a desired shape (e.g., cylindrical, rectangular, laminated, button, etc.) and inserted into a container of the desired shape. Next, a nonaqueous electrolyte is injected into the container, so that the electrolyte is impregnated into each pore in the separator and the gaps in the positive and negative electrodes. This completes the production of a lithium ion secondary battery.
[0048] 4. Effects of this embodiment The nonaqueous electrolyte secondary battery configured as described above can sufficiently suppress an increase in the internal temperature of the nonaqueous electrolyte secondary battery even in an environment in which the internal temperature is likely to increase due to a battery abnormality such as an internal short circuit, and further can suppress deterioration of the cycle characteristics of the nonaqueous electrolyte secondary battery due to the inclusion of a heat-inhibiting additive that suppresses heat generation.
[0049] <5. Other embodiments of the present invention> The present invention is not limited to the above-described embodiment. In the above embodiment, the positive electrode contains the composite particles according to the present invention, but the negative electrode may contain the composite particles. When the negative electrode contains the composite particles, it is preferable that the content of the composite particles is the same as that of the positive electrode. The composite particles may be contained in the electrolyte, or may be contained in a plurality of locations among the positive electrode, the negative electrode, and the electrolyte. When the negative electrode contains the composite particles for a non-aqueous electrolyte secondary battery, the content of the composite particles for a non-aqueous electrolyte secondary battery relative to the entire negative electrode is preferably in the same range as that of the positive electrode.When the electrolytic solution contains the composite particles for a non-aqueous electrolyte secondary battery, the content of the composite particles for a non-aqueous electrolyte secondary battery is preferably in the range of 0.1% by mass or more and 10.0% by mass or less, where the mass of the entire electrolytic solution is taken as 100% by mass. Needless to say, the present invention is not limited to these embodiments, and various modifications are possible without departing from the spirit of the present invention. EXAMPLES
[0050] The present invention will be described in more detail below with reference to specific examples. However, the following examples are merely examples of the present invention, and the present invention is not limited to the following examples.
[0051] <Preparation of composite particles> Example 1 As a starting material, aluminum hydroxide (D50: 3.0 μm, BET specific surface area: 205 m 2 1.0 g of phenyl phosphate (Pb / g), 2.5 g of phenyl phosphate, and 2.5 g of phosphonic acid were dispersed in 50 cc of a mixed solution of ethanol and purified water (mixing ratio 1:1). After heating this dispersion at 70°C for 24 hours, it was filtered with water and ethanol, washed with water and ethanol, and the solid on the filter paper was vacuum dried to obtain composite particles AA.
[0052] Example 2 As the starting material, aluminum hydroxide (D50: 3.0 μm, BET specific surface area: 205 m 2 Composite particles AB were obtained in the same manner as in Example 1, except that 1.0 g of phosphate buffer solution (pH 7.0 / g), 2.5 g of diphenyl phosphate, and 2.5 g of phosphonic acid were used.
[0053] Example 3 As the starting material, aluminum hydroxide (D50: 3.0 μm, BET specific surface area: 205 m 2Composite particles (AC) were obtained by the same procedure as in Example 1, except that 1.0 g of (CuO / g), 2.5 g of triphenyl phosphate, and 2.5 g of phosphonic acid were used.
[0054] Example 4 As the starting material, aluminum hydroxide (D50: 3.0 μm, BET specific surface area: 205 m 2 Composite particles (AD) were obtained by the same procedure as in Example 1, except that 1.0 g of phosphate buffer solution (pH 7.0 / g), 2.5 g of phenylphosphonic acid, and 2.5 g of phosphonic acid were used.
[0055] Example 5 As the starting material, aluminum hydroxide (D50: 3.0 μm, BET specific surface area: 205 m 2 Composite particles (AE) were obtained by the same procedure as in Example 1, except that 1.0 g of phenylphosphonic acid ( / g), 2.5 g of phenylphosphonic acid, and 2.5 g of phosphoric acid were used.
[0056] Example 6 As the starting material, aluminum hydroxide (D50: 3.0 μm, BET specific surface area: 205 m 2 Composite particles (AF) were obtained by the same procedure as in Example 1, except that 1.0 g of phenylphosphonic acid ( / g), 2.5 g of phenylphosphonic acid, and 2.5 g of methylphosphinic acid were used.
[0057] Example 7 As the starting material, aluminum hydroxide (D50: 3.0 μm, BET specific surface area: 205 m 2 Composite particles (AG) were obtained by the same procedure as in Example 1, except that 1.0 g of the phosphate buffer solution (pH 7.0 / g), 2.5 g of phenylphosphonic acid, and 2.5 g of methylphosphonic acid were used.
[0058] Example 8 Activated alumina (D50: 3.0 μm, BET specific surface area: 300 m) was used as the starting material. 2 Composite particles (BA) were obtained by the same procedure as in Example 1, except that 1.0 g of (pH 7.0 / g), 2.5 g of phenyl phosphate, and 2.5 g of phosphonic acid were used.
[0059] Example 9 Activated alumina (D50: 3.0 μm, BET specific surface area: 300 m) was used as the starting material. 2 Composite particles (BB) were obtained by the same procedure as in Example 1, except that 1.0 g of the binder resin (CuO2 / g), 2.5 g of diphenyl phosphate, and 2.5 g of phosphonic acid were used.
[0060] Example 10 Activated alumina (D50: 3.0 μm, BET specific surface area: 300 m) was used as the starting material. 2 Composite particles (BC) were obtained by the same procedure as in Example 1, except that 1.0 g of (CuO / g), 2.5 g of triphenyl phosphate, and 2.5 g of phosphonic acid were used.
[0061] Example 11 Activated alumina (D50: 3.0 μm, BET specific surface area: 300 m) was used as the starting material. 2 Composite particles (BD) were obtained by the same procedure as in Example 1, except that 1.0 g of the binder resin (polymerizable monomer / g), 2.5 g of phenylphosphonic acid, and 2.5 g of phosphonic acid were used.
[0062] Example 12 Activated alumina (D50: 3.0 μm, BET specific surface area: 300 m) was used as the starting material. 2 Composite particles (BE) were obtained by the same procedure as in Example 1, except that 1.0 g of phenylphosphonic acid (pH 7.0 / g), 2.5 g of phenylphosphonic acid, and 2.5 g of phosphoric acid were used.
[0063] (Example 13) Activated alumina (D50: 3.0 μm, BET specific surface area: 300 m) was used as the starting material. 2 Composite particles (BF) were obtained by the same procedure as in Example 1, except that 1.0 g of the cation exchange resin (Pb / g), 2.5 g of phenylphosphonic acid, and 2.5 g of methylphosphinic acid were used.
[0064] Example 14 Activated alumina (D50: 3.0 μm, BET specific surface area: 300 m) was used as the starting material. 2Composite particles (BG) were obtained by the same procedure as in Example 1, except that 1.0 g of phosphate buffer solution / g, 2.5 g of phenylphosphonic acid, and 2.5 g of methylphosphonic acid were used.
[0065] Example 15 The starting material was kaolinite (Al2Si2O5(OH)4, D50: 1.0 μm, BET specific surface area: 120 m 2 Composite particles (CA) were obtained by the same procedure as in Example 1, except that 1.0 g of the phosphate buffer solution (pH 7.0 / g), 2.5 g of phenyl phosphate, and 2.5 g of phosphonic acid were used.
[0066] Example 16 The starting material was kaolinite (Al2Si2O5(OH)4, D50: 1.0 μm, BET specific surface area: 120 m 2 Composite particles (CB) were obtained by the same procedure as in Example 1, except that 1.0 g of (CuO / g), 2.5 g of diphenyl phosphate, and 2.5 g of phosphonic acid were used.
[0067] (Example 17) The starting material was kaolinite (Al2Si2O5(OH)4, D50: 1.0 μm, BET specific surface area: 120 m 2 Composite particles (CC) were obtained by the same procedure as in Example 1, except that 1.0 g of (CuO / g), 2.5 g of triphenyl phosphate, and 2.5 g of phosphonic acid were used.
[0068] (Example 18) The starting material was kaolinite (Al2Si2O5(OH)4, D50: 1.0 μm, BET specific surface area: 120 m 2 Composite particles (CD) were obtained by the same procedure as in Example 1, except that 1.0 g of the polymerizable monomer (C1, C2, C3, C4) was used, 2.5 g of phenylphosphonic acid, and 2.5 g of phosphonic acid.
[0069] (Example 19) The starting material was kaolinite (Al2Si2O5(OH)4, D50: 1.0 μm, BET specific surface area: 120 m 2Composite particles (CE) were obtained by the same procedure as in Example 1, except that 1.0 g of cellulose acetate / g, 2.5 g of phenylphosphonic acid, and 2.5 g of phosphoric acid were used.
[0070] (Example 20) The starting material was kaolinite (Al2Si2O5(OH)4, D50: 1.0 μm, BET specific surface area: 120 m 2 Composite particles (CF) were obtained by the same procedure as in Example 1, except that 1.0 g of phenylphosphonic acid ( / g), 2.5 g of phenylphosphonic acid, and 2.5 g of methylphosphinic acid were used.
[0071] Example 21 The starting material was kaolinite (Al2Si2O5(OH)4, D50: 1.0 μm, BET specific surface area: 120 m 2 Composite particles (CG) were obtained by the same procedure as in Example 1, except that 1.0 g of the phosphate buffer solution (pH 7.0 / g), 2.5 g of phenylphosphonic acid, and 2.5 g of methylphosphonic acid were used.
[0072] Example 22 As the starting material, pseudoboehmite (D50: 1.0 μm, BET specific surface area: 384 m 2 Composite particles (DA) were obtained by the same procedure as in Example 1, except that 1.0 g of (CuO / g), 2.5 g of phenyl phosphate, and 2.5 g of phosphonic acid were used.
[0073] Example 23 As the starting material, pseudoboehmite (D50: 1.0 μm, BET specific surface area: 384 m 2 Composite particles (DB) were obtained by the same procedure as in Example 1, except that 1.0 g of (CuO / g), 2.5 g of diphenyl phosphate, and 2.5 g of phosphonic acid were used.
[0074] (Example 24) As the starting material, pseudoboehmite (D50: 1.0 μm, BET specific surface area: 384 m 2 Composite particles (DC) were obtained by the same procedure as in Example 1, except that 1.0 g of (CuO / g), 2.5 g of triphenyl phosphate, and 2.5 g of phosphonic acid were used.
[0075] (Example 25) As the starting material, pseudoboehmite (D50: 1.0 μm, BET specific surface area: 384 m 2 Composite particles (DD) were obtained by the same procedure as in Example 1, except that 1.0 g of the hydroxyl group-containing polymer (C10 / g), 2.5 g of phenylphosphonic acid, and 2.5 g of phosphonic acid were used.
[0076] (Example 26) As the starting material, pseudoboehmite (D50: 1.0 μm, BET specific surface area: 384 m 2 Composite particles (DE) were obtained by the same procedure as in Example 1, except that 1.0 g of dimethylformamide (DMSO) was used, 2.5 g of phenylphosphonic acid, and 2.5 g of phosphoric acid were used.
[0077] Example 27 As the starting material, pseudoboehmite (D50: 1.0 μm, BET specific surface area: 384 m 2 Composite particles (DF) were obtained by the same procedure as in Example 1, except that 1.0 g of (polyoxyethylene ether) / g, 2.5 g of phenylphosphonic acid, and 2.5 g of methylphosphinic acid were used.
[0078] (Example 28) As the starting material, pseudoboehmite (D50: 1.0 μm, BET specific surface area: 384 m 2 Composite particles (DG) were obtained by the same procedure as in Example 1, except that 1.0 g of phosphate buffer solution (pH 7.0 / g), 2.5 g of phenylphosphonic acid, and 2.5 g of methylphosphonic acid were used.
[0079] (Example 29) As the starting material, pseudoboehmite (D50: 1.0 μm, BET specific surface area: 384 m 2 Composite particles (DH) were obtained by the same procedure as in Example 1, except that 1.0 g of the hydroxyl group-containing polymer (pH 7.0 / g), 2.5 g of phenylphosphonic acid, and 5.0 g of phosphoric acid were used.
[0080] (Example 30) As the starting material, pseudoboehmite (D50: 1.0 μm, BET specific surface area: 384 m 2Composite particles (EA) were obtained by the same procedure as in Example 1, except that 1.0 g of (amount per unit area / g), 2.5 g of phenyl phosphate, and 2.5 g of boric acid were used.
[0081] (Example 31) As the starting material, pseudoboehmite (D50: 1.0 μm, BET specific surface area: 384 m 2 Composite particles (EB) were obtained by the same procedure as in Example 1, except that 1.0 g of the binder resin (polymerizable monomer / g), 2.5 g of phenylphosphonic acid, and 2.5 g of boric acid were used.
[0082] Example 32 As the starting material, pseudoboehmite (D50: 1.0 μm, BET specific surface area: 384 m 2 Composite particles (EC) were obtained by the same procedure as in Example 1, except that 1.0 g of (CuO / g), 2.5 g of phenyl phosphate, and 2.5 g of boronic acid were used.
[0083] (Example 33) As the starting material, pseudoboehmite (D50: 1.0 μm, BET specific surface area: 384 m 2 Composite particles (ED) were obtained by the same procedure as in Example 1, except that 1.0 g of the polymerizable monomer (polymerizable compound / g), 2.5 g of phenylphosphonic acid, and 2.5 g of boronic acid were used.
[0084] (Example 34) As the starting material, pseudoboehmite (D50: 1.0 μm, BET specific surface area: 384 m 2 Composite particles (FA) were obtained by the same procedure as in Example 1, except that 1.0 g of (1.0 g / g) phenyl phosphate, 2.5 g of bromic acid, and 2.5 g of phenyl phosphate were used.
[0085] Example 35 As the starting material, pseudoboehmite (D50: 1.0 μm, BET specific surface area: 384 m 2 Composite particles (FB) were obtained by the same procedure as in Example 1, except that 1.0 g of (pH 7.0 / g), 2.5 g of phenylphosphonic acid, and 2.5 g of bromic acid were used.
[0086] Comparative Example 5 As the starting material, aluminum hydroxide (D50: 3.0 μm, BET specific surface area: 205 m 2 Composite particles (GA) were obtained by the same procedure as in Example 1, except that 1.0 g of phenylphosphonic acid (1.0 g / g) and 5.0 g of phenylphosphonic acid were used.
[0087] Comparative Example 6 As the starting material, aluminum hydroxide (D50: 3.0 μm, BET specific surface area: 205 m 2 Composite particles (GB) were obtained by the same procedure as in Example 1, except that 1.0 g of 1.0 g of dimethylformamide (DMF) and 5.0 g of diphenyl phosphate were used.
[0088] <Preparation of positive electrode> (Examples 1-35, Comparative Examples 2-6) LiCoO2, acetylene black, polyvinylidene fluoride, and the composite particles, metal hydroxide particles, or flame retardant shown in Table 1 (composite particles, metal hydroxide particles, and flame retardants are also collectively referred to as heat suppressing additives) were dispersed and mixed in N-methyl-2-pyrrolidone solvent in a mass ratio of 97.0:1.0:1.3:0.7 as dry powder (solid content) not containing solvent, to prepare a positive electrode mixture slurry. Next, the mixture coating amount (area density) after drying was 20.0 mg / cm on one side. 2 The slurry was applied to one or both sides of an aluminum current collector so that the density of the positive electrode mixture layer became 4.15 g / cc, and then the resulting mixture was pressed with a roll press machine so that the density of the positive electrode mixture layer became 4.15 g / cc to prepare a positive electrode.
[0089] Comparative Example 1 A positive electrode was prepared in the same manner as in Example 1, except that a positive electrode mixture slurry was prepared by dispersing and mixing LiCoO, acetylene black, and polyvinylidene fluoride in an N-methyl-2-pyrrolidone solvent in a mass ratio of 97.7:1.0:1.3 as dry powders (solid contents) not including a solvent.
[0090] <Negative electrode production> (Examples 1-35, Comparative Examples 1-6) The negative electrode mixture slurry was prepared by dissolving and dispersing artificial graphite, sodium carboxymethylcellulose (CMC), and styrene butadiene-based aqueous dispersion in an aqueous solvent in a mass ratio of 97.5:1.0:1.5 as dry powder (solid content) without solvent. Then, the mixture coating amount (area density) after drying was 15.0 mg / cm. 2 The negative electrode mixture slurry was applied to one or both sides of a copper foil so as to obtain a negative electrode mixture layer density of 1.65 g / cc, and then pressed with a roll press machine so as to obtain a negative electrode mixture layer density of 1.65 g / cc.
[0091] <Secondary battery cell production> (Examples 1-35, Comparative Examples 1-6) An electrode laminate was prepared by laminating multiple positive and negative electrodes with a polypropylene porous separator between them so that the battery design capacity was 300 mAh. At this time, the positive and negative electrodes arranged inside the electrode laminate had a composite layer formed on both sides of the current collector, and the positive or negative electrode arranged on the outermost layer had a composite layer formed on only one side. Specifically, the electrode plate area was 8.5 cm2. 2 The positive electrode (five on each side) and the electrode surface area are 10.0 cm 2 Then, nickel and aluminum lead wires were welded to the negative and positive electrodes of the electrode stack in the aluminum laminate film, respectively, and the lead wires were then pulled out and stored in the aluminum laminate film. An electrolyte was poured in and the battery was sealed under reduced pressure to prepare a pre-initial charge secondary battery cell. The electrolyte used was a mixture of ethylene carbonate / dimethyl carbonate / fluoroethylene carbonate in a 15 / 80 / 5 (volume ratio) solvent in which 1.3M LiPF6 and 1% by mass of vinylene carbonate were dissolved.
[0092] <Evaluation of antipyretic additives> The heat-inhibiting additives used in the Examples and Comparative Examples were evaluated as follows. (Elemental analysis) An inductively coupled plasma atomic emission spectrometer (ICP-AES, Agilent Technologies, Agilent 5110 VDV type) was used to measure in accordance with JIS K0116:2014, and the Al, P, B, and Br elements contained in the composite particles, metal hydroxide particles, or radical scavengers of each Example and Comparative Example were quantitatively analyzed.
[0093] (BET specific surface area) The specific surface area of metal hydroxide particles or composite particles (BET specific surface area calculated based on the adsorption isotherm measured by adsorbing water vapor) was measured using a gas adsorption measurement device (BELSORP, manufactured by Microtrack-Bell) in accordance with JIS K6217-2.
[0094] (Amount of desorbed gas) Thermal desorption mass spectrometry (TDS-MS) was performed using a thermal desorption analyzer TDS-1200 manufactured by Electro Scientific Co., Ltd., to measure and analyze the amounts of desorbed methane (CH4) molecules, methanol (CH3OH) molecules, benzene (C6H6) molecules, diphosphorus (P2) molecules, and water (H2O) molecules as follows. In the TDS, the sample stage on which the negative electrode active material was set was made of quartz, and the sample dish was made of SiC. The heating rate was 60°C / min. The heating was controlled by monitoring the surface temperature of the sample. The sample weight was 1 mg, and was corrected by the actual measured weight. A quadrupole mass spectrometer was used for detection, and the applied voltage was 1000V. The amount of each gas (μmol / g) desorbed from metal hydroxide particles or composite particles was measured by TDS as the temperature increased from 80°C to 1400°C. The mass numbers [M / z] used in the analysis of the measured values were 15 for CH4, 18 for H2O, 31 for CH3OH, 62 for P2, and 78 for C6H6, and the gases corresponding to the above mass numbers were all considered to be the above substances. Here, for the amount of H2O gas, only the integrated value from 80°C to 200°C was used from the results over the entire temperature range, and this was taken to be the amount of desorbed H2O (MS2).
[0095] (Evaluation of particle size) The particle size of the composite particles or metal hydroxide particles was evaluated as the integrated value 50% (D50) of the particle size distribution based on the volume of the particle size in the particle size distribution obtained by a laser diffraction / scattering method. D50 was measured using the following device and conditions. Measurement equipment: Laser diffraction / scattering type particle size distribution measurement equipment MT3300 (manufactured by Microtrack Bell Co., Ltd.) Transparency: Transparent Shape: non-spherical Circulation speed: 7 Measurement time: 30 seconds Number of iterations: 3 Refractive index: a. Composite particles, metal hydroxide particles or particle mixture: 1.65 b. Ethanol solvent: 1.36
[0096] [Evaluation of secondary batteries] (Cycle characteristics) The secondary battery cells prepared in Examples 1 to 35 and Comparative Examples 1 to 6 were charged at a constant current of 0.1 CA to 4.4 V of the design capacity in a thermostatic chamber at 25 ° C., and then charged at a constant voltage of 4.4 V to 0.05 CA. Thereafter, constant current discharge was performed at 0.1 CA to 3.0 V. Furthermore, in a thermostatic chamber at 25 ° C., one cycle of constant current charging at 0.2 CA, constant voltage charging at 0.05 CA, and constant current discharging at 0.2 CA was performed under the conditions of a charge end voltage of 4.4 V and a discharge end voltage of 3.0 V, and the initial discharge capacity was measured. The secondary battery cells were subjected to a life test of 200 cycles of constant current charging at 0.5 CA, constant voltage charging at 0.05 CA, and constant current discharging at 0.5 CA under the conditions of a charge end voltage of 4.4 V and a discharge end voltage of 3.0 V at a temperature of 45 ° C. After 200 cycles, the discharge capacity was measured at a constant current charge of 0.2 CA, a constant voltage charge of 0.05 CA, and a discharge of 0.2 CA, and divided by the initial discharge capacity to calculate the capacity retention rate after 200 cycles.
[0097] (Heating test) The secondary battery cells prepared in Examples 1 to 35 and Comparative Examples 1 to 6 were charged at a constant current of 0.1 CA, which is the design capacity, to 4.4 V in a thermostatic chamber at 25 ° C., and then charged at a constant voltage of 0.05 CA at 4.4 V. Thereafter, constant current discharge was performed at 0.1 CA to 3.0 V. Furthermore, in a thermostatic chamber at 25 ° C., constant current charging was performed at 0.2 CA, constant voltage charging at 0.05 CA, and constant current discharging at 0.2 CA was performed for one cycle under the conditions of a charge end voltage of 4.4 V and a discharge end voltage of 3.0 V, and then the cell was charged at a constant current / constant voltage again to 4.4 V to be used as an initial cell. This secondary battery cell was left in a thermostatic chamber heated to 165 ° C. for one hour, and the case where the battery voltage became 4.2 V or less was regarded as "abnormal occurrence", and the abnormality occurrence rate of 10 battery tests was evaluated.
[0098] (Nail penetration test) For the initial cell described above, a nail penetration test was conducted by inserting a 3 mm diameter nail into the center of the cell at a speed of 1 mm / s. If the external temperature of the battery reached 50°C or higher 5 seconds after the nail was inserted, this was deemed to be an "abnormality," and the rate of abnormality occurrence was evaluated for 10 tested batteries.
[0099] (Overcharge test) The initial cell described above was further charged at a constant current of 3 CA up to 12 V. If the external temperature of the battery after 10 minutes of constant voltage charging after reaching 12 V reached 50°C or higher, this was deemed to be an "abnormality." The abnormality occurrence rate of the 10 tested batteries was evaluated.
[0100] (Evaluation Results) The types and physical properties of the heat-inhibiting additives used in the above-described Examples and Comparative Examples are shown in Table 1. In addition, the evaluation results for the secondary battery cells of Examples 1 to 35 and Comparative Examples 1 to 6 are summarized in Table 2.
[0101] [Table 1]
[0102] [Table 2]
[0103] FIG. 1 shows a graph of the discharge capacity retention rates for the secondary battery cells produced in Example 26, Comparative Example 1, and Comparative Examples 3 to 5 shown in Tables 1 and 2.
[0104] <Confirmation of heat generation behavior in the presence of charging positive electrode and electrolyte> The initial cells of the secondary battery cells prepared in Example 26, Comparative Example 1, and Comparative Examples 3 to 5 shown in Tables 1 and 2 and fully charged were disassembled in a glove box, and the positive electrode was washed with dimethyl carbonate solvent and dried to obtain a positive electrode, which was designated as a "charged positive electrode." 2.0 mg of the "charged positive electrode" and 1.0 mg of the same electrolyte solution used in preparing the secondary battery cells were placed in a special sealed container and crimped, and then the temperature was increased at a temperature increase rate of 5K / min using a differential scanning calorimeter DSC (manufactured by Hitachi High-Tech Science Corporation) in accordance with the provisions of JIS K7121, and the heat generation behavior was evaluated. The results are shown in Figure 2.
[0105] <Considerations on Examples and Comparative Examples> From the results in Table 2, in Examples 1 to 35, the occurrence rate of abnormalities caused by temperature rises inside the battery could be sufficiently suppressed to a low level even under high temperature conditions during high voltage charging, external impacts such as nail penetration, overcharging, and other conditions that tend to increase the internal temperature of the battery. This effect can also be seen from the disappearance of the heat generation peak between 150°C and 250°C in the heat generation behavior in Figure 2. In contrast, the abnormality rate exceeded 40% in Comparative Example 1, which did not contain a heat-suppressing additive, and Comparative Examples 2 to 4, which contained only one of a metal hydroxide or a flame retardant, as well as in Comparative Examples 5 and 6, which contained composite particles in which a metal hydroxide and a flame retardant were combined, but in which the total content of phosphorus or phosphorus and boron or bromine in the composite particles was less than 18 mass%. Note that, although equal amounts of two types of flame retardants were added in each example, the present invention is not limited to this embodiment, and the effects of the present invention can be achieved by adjusting the total content of phosphorus or phosphorus and boron or bromine in the composite particles to 18 mass% or more and 30 mass% or less. Furthermore, from the results of Table 2 and FIG. 1, it can be seen that in Comparative Examples 2 to 4, the inclusion of various heat-inhibiting additives results in lower cycle characteristics than in Comparative Example 1, which does not contain a heat-inhibiting additive, but in Examples 1 to 35, cycle characteristics equivalent to that of Comparative Example 1 are maintained.
Claims
1. A composite particle for a non-aqueous electrolyte secondary battery, comprising a metal hydroxide and a flame retardant component, The flame retardant component contains phosphorus, phosphorus and boron, or phosphorus and bromine, The composite particles for a non-aqueous electrolyte secondary battery have a phosphorus element content, a combined content of phosphorus and boron elements, or a combined content of phosphorus and bromine elements of 18% by mass or more and 30% by mass or less, based on 100% by mass of the composite particles for a non-aqueous electrolyte secondary battery.
2. Desorption P from 80°C to 1400°C using a temperature programmed desorption mass spectrometer (TDS-MS) 2 Amount (MS1) is 600 x 10 -6 mol / g or more 2000×10 -6 mol / g or less, and the desorption H from 80°C to 200°C by TDS-MS 2 O amount (MS2) is 50 x 10 -6 mol / g or more 1000×10 -6 2. The composite particles for a non-aqueous electrolyte secondary battery according to claim 1, wherein the molecular weight of the composite particle is 1000 or less.
3. CH desorption from 80 to 1400 °C by TDS-MS 4 Amount (MS3) is 30 x 10 -6 mol / g or more 400×10 -6 mol / g or less, and the CH desorption from 80°C to 1400°C by TDS-MS 3 OH amount (MS4) is 500 x 10 -6 mol / g or more 2500×10 -6 mol / g or less, and desorption C from 80 °C to 1400 °C by TDS-MS 6 H 6 Amount (MS5) is 100 x 10 -6 mol / g or more 2500×10 -6 2. The composite particles for a non-aqueous electrolyte secondary battery according to claim 1, wherein the molecular weight of the composite particle is 1000 or less.
4. The composite particles for a nonaqueous electrolyte secondary battery according to claim 2 , wherein the ratio of the amount of desorbed gas satisfies the following formula (1): 0.6≦(MS1 / MS2)≦10.0...(1)
5. The BET specific surface area calculated from the adsorption isotherm measured by adsorbing nitrogen is 8 m 2 / g or more 80m 2 The composite particles for a non-aqueous electrolyte secondary battery according to claim 1 , wherein the molecular weight of the composite particles is 1 / g or less.
6. 2. The composite particle for a non-aqueous electrolyte secondary battery according to claim 1, wherein the integrated value 50% (D50) of the volume-based particle size distribution of the composite particle is 0.05 μm or more and 10 μm or less.
7. 2. The composite particle for a non-aqueous electrolyte secondary battery according to claim 1, wherein the metal hydroxide comprises at least one selected from the group consisting of aluminum hydroxide, pseudoboehmite, boehmite, activated alumina, and kaolinite.
8. 2. The composite particles for a non-aqueous electrolyte secondary battery according to claim 1, wherein the content of aluminum element measured by inductively coupled plasma atomic emission spectrometry (ICP-AES) is 5% by mass or more and 30% by mass or less.
9. A positive electrode for a non-aqueous electrolyte secondary battery comprising a positive electrode current collector and a positive electrode mixture layer laminated on the positive electrode current collector, A positive electrode for a non-aqueous electrolyte secondary battery, wherein the positive electrode mixture layer contains a positive electrode active material and the composite particle for a non-aqueous electrolyte secondary battery according to any one of claims 1 to 8.
10. A non-aqueous electrolyte secondary battery comprising a positive electrode, a negative electrode, a separator, and a non-aqueous electrolyte solution, The positive electrode of claim 9 .
11. A method for producing the composite particles for a non-aqueous electrolyte secondary battery according to claim 1, A method for producing composite particles for a non-aqueous electrolyte secondary battery, comprising a step of mixing metal hydroxide particles and a flame retardant and heating the mixture.
Citation Information
Patent Citations
Lithium secondary battery
JP2011159484A
Lithium ion battery
JP2011258481A
Electrolyte, battery, battery pack, electronic apparatus, electric vehicle, power storage device and power system
JP2016162528A